2019
DOI: 10.1136/bcr-2018-227677
|View full text |Cite
|
Sign up to set email alerts
|

Maculopathy from an accidental exposure to welding arc

Abstract: Welding light can cause photic retinal injury. We report binocular maculopathy induced by a brief exposure to electric arc welding light in a patient who could not equipped with protective device because of narrow space. A 47-year-old man performed electric arc welding for approximately 10–15 min without wearing protective device because of narrow space and subsequently experienced eye discomfort and decreased visual acuity. At the initial visit, his best corrected visual acuity was 0.5. Fundus examination, op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…A review of the existing literature [6][7][8][9][10][11][12][13][14] reveals that the ophthalmoscopic appearance and clinical course in our patients are similar to those seen in solar or welder's maculopathy, both of which are characterized by a photochemical type of damage to the outer retina. We have shown that they also have similar OCT characteristics both in acute and chronic stages, suggesting that they may share the same putative phototoxic etiology.…”
Section: Discussionsupporting
confidence: 59%
“…A review of the existing literature [6][7][8][9][10][11][12][13][14] reveals that the ophthalmoscopic appearance and clinical course in our patients are similar to those seen in solar or welder's maculopathy, both of which are characterized by a photochemical type of damage to the outer retina. We have shown that they also have similar OCT characteristics both in acute and chronic stages, suggesting that they may share the same putative phototoxic etiology.…”
Section: Discussionsupporting
confidence: 59%
“…The pathophysiology and signs and symptoms are again similar to those seen with the other photic retinopathy conditions. 21 Our patient again denied any history of welding or exposure to lasers used in welding. Physicians should also note if one or both eyes are involved.…”
Section: Discussionmentioning
confidence: 87%
“…A much more frequent observation of ocular injury associated with welding arc use is photoelectric keratitis, often referred as "weld-erʼs eye" or "welderʼs flash" after unprotected exposure against emission in the ultraviolet spectrum, which is absorbed by the cornea and conjunctiva. Depending on the spectral range transmitted to the eye, either photoelectric keratitis or welding arc maculopathy or both together may develop [7]. Recent progress in posterior eye segment imaging has led to a precise characterization of typical outer retinal findings in welding arc maculopathy.…”
Section: Discussionmentioning
confidence: 99%